2022
DOI: 10.1101/2022.07.14.500096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammatory Signaling in Pancreatic Cancer Transfers Between a Single-cell RNA Sequencing Atlas and Co-Culture

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a devastating malignancy driven by a heterogeneous tumor microenvironment enriched with cancer associated fibroblasts (CAFs) that influence its overall immunosuppressive composition. We examined inflammation in PDAC by leveraging our existing patient-derived organoid (PDO) model and a novel PDO-CAF co-culture. We first identified induction of major histocompatibility complex class II expression following treatment with interferon gamma. In parallel, we collated an atl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…We observed that the reduction in this inflammation pattern is gradual with progression from normal ductal cells through LG to HG PanIN lesions. It is possible that downregulation of this pattern may be due to development of immune suppressive CAFs that are already present in PanINs and are functionally similar to those present in PDACs, as demonstrated by Kinny-Koster et al using a co-culture patient derived organoid model(18). In addition, CAFs can create an immunosuppressive TME by producing and releasing cytokines that inhibits immune cell infiltration and factors that provide cancer cells additional growth and survival advantages(21,23).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We observed that the reduction in this inflammation pattern is gradual with progression from normal ductal cells through LG to HG PanIN lesions. It is possible that downregulation of this pattern may be due to development of immune suppressive CAFs that are already present in PanINs and are functionally similar to those present in PDACs, as demonstrated by Kinny-Koster et al using a co-culture patient derived organoid model(18). In addition, CAFs can create an immunosuppressive TME by producing and releasing cytokines that inhibits immune cell infiltration and factors that provide cancer cells additional growth and survival advantages(21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a second transfer learning method was required to uncover PDAC scRNA-seq patterns from the PanIN ST data. Adding to the learned oncogenic and a normal pancreatic function patterns (Patterns 5 and 2, respectively) in the PDAC atlas (18), our approach identified a third pattern enriched for inflammation markers (Pattern 7) that is downregulated in primary PDAC cells. This reduction in inflammatory signals may be one mechanism by which PDACs evade immune recognition, as tumor cells will be producing less immune chemoattractants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations